GAMBARAN UROBILINOGEN PADA MASYARAKAT YANG MENGONSUMSI KAMEKO DI KELURAHAN MANGGA DUA KOTA KENDARI - Idris, Sri Aprilianti; Balaka, Kemal Idris; Santoso, Edwin (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2022)
Urobilinogen is a by-product formed by the reduction of bilirubin and is a colorless component produced by bacteria in bilirubin in the intestine. Determination of the amount of urobilinogen excreted in a given period allows to help in diagnosing liver dysfunction. Kameko is a drink containing ethanol made from fermented sap then mixed with mangrove wood. The consumption of kameko alcohol is at risk for impaired liver function, which is divided into fatty liver (fatty liver), alcoholic hepatitis (alcoholic hepatitis), and cirrhosis (cirrhosis). The purpose of this study was to determine the description of urobilinogen in people who consume kameko alcohol in Mangga Dua Village Kendari City. The method used in this study is an analitik descriptif, method with purposive sampling, which has the categories of male population, age 18-40 years, and duration of consuming kameko at least 2-10 years and sample examination is carried out using a Urine Analyzer ( Verify U120). The results showed that, from a total of 32 patients who underwent examination, 14 patients had urine urobilinogen levels of 0.2 mg/dL and 18 patients had urine urobilinogen levels of 1.0 mg/dL. Urine urobilinogen levels in 32 patients were normal, ie 0.2-1.0 mg/dL. Key Words : Urobilinogen, Kameko, Mangga Dua Village